Od gry dramatycznej do kształcenia krytycznego odbiorcy środków masowego przekazu - refleksja o współczesnej dydaktyce francuskiej = From role-playing to educating a critical receiver of mass-media - some ideas about contemporary french didactics - Dyduch, Barbara (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The basis of the present work are the ideas which are the result of observations of role-playing arranged for the purpose of mother tongue teaching in French schools of college and lycee type in the school year 1978/9.
Keywords: środki masowego przekazu; dydaktyka; Francja; 20 w.